Transient heat transfer analysis of an orthotropic composite plate with oblique cracks using dual-phase-lagging model. (1st November 2022) - Wen, Zhuoxin; Hou, Chi; Zhao, Meiying; Wan, Xiaopeng
Abstract: Cracks have a significant effect on heat transfer in composites, yet the influence of oblique cracks on the temperature response of composites has not been fully investigated under strong transient thermal shock, in which the heat propagation velocity cannot be assumed to be infinite. In this work, the dual-phase-lagging heat transfer model is employed to capture the transient temperature response. By imposing different boundary conditions on the crack surface, an extended boundary correction algorithm has been derived to avoid the problem of non-convergence when dealing with large and small angle cracks. The effects of crack orientation angle and interaction between cracks on dual-phase-lagging heat conduction in orthotropic materials are analyzed at the macroscale. For the two-dimensional representative volume element (RVE) of fiber reinforced composite material, the influence of the multi-crack distribution on dual-phase-lagging heat conduction at the mesoscale is further discussed in detail.